A revision of trifoliolate Indigofera (Tribe Indigofereae: Fabaceae) in India - Chauhan, Vibha; Pandey, Arun (Phytotaxa, 2015)
A revision of trifoliolate Indigofera in India is provided based on field studies, and examination of herbarium specimens. In India, 11 species and 4 varieties of trifoliolate Indigofera are recognized: Indigofera barberi, I. deccanensis, I. glandulosa, I. glandulosa var. sykesii, I. karuppiana, I. pedicellata, I. prostrata, I. santapaui, I. thothathrii, I. tirunelvelica, I. trifoliata, I. trifoliata var. duthiei, I. trita, I. trita var. maffeii and I. trita var. purandharensis. Of 11 species, seven species and three varieties are endemic. A key to the species, description and illustrations are provided along with data on flowering and fruiting, distribution, habitat, chromosome number, and ethnobotanical uses.